Pediatric postural orthostatic tachycardia syndrome: From mechanisms to individualized management - Wenrui Xu; Hongfang Jin; Ying Liao; Junbao Du (Pediatric Discovery)
Abstract Postural orthostatic tachycardia syndrome (POTS) represents chronic orthostatic intolerance. Patients usually suffer from presyncopal symptoms, such as lightheadedness, headache, blurred vision, and fatigue. Central hypovolemia, peripheral vascular dysfunction, and a hyperadrenergic state may contribute to the pathogenesis of POTS. It is necessary to comprehensively assess the clinical characteristics, physiological changes, and biochemical markers to select an appropriate therapy. Since the introduction of the concept of individualized treatment for POTS, great progress has been made in the field.